Bolivian Teachers’ Agency: Soldiers of Liberation or Guards of Coloniality and Continuation? - Lopes Cardozo, Mieke T. A. (Education Policy Analysis Archives, 2015)
This paper investigates the problems and promises of teachers’ agency associated with Bolivia’s current “decolonising” education reform. The Avelino Siñani Elizardo Pérez (ASEP) education reform is part of a counter-hegemonic and anti-neoliberal policy that aims to advance the political project of the government of Evo Morales, with teachers as its most strategic leading card. The article draws on theoretical insights from the Strategic Relational Approach (SRA) and applies this frame to analyse teachers’ agency for change in Bolivia’s contemporary socio-political context. This framework allows for a critical reflection of current discourses and educators’ efforts to decolonize the education system, in a context of political and societal tensions and inequalities. The article argues that the current political discourse and socio-political changes open up some spaces for teachers’ agency. However, the reality in rather conservative teacher education institutions and schools, together with teachers’ daily struggle for survival, provide serious constraints for teachers to become “committed or transformative intellectuals”.